On the Dating of the Ethiopian Dynastic Treatise Kǝbrä nägäśt: New Evidence - Frantsouzoff, Serge A. (Scrinium, 2016)
The present article argues the garbled text of the Lev. 18:8 as found in the Ethiopian dynastic treatise Kǝbrä nägäśt to be intentional. It refers to the conflict between the King of Ethiopia ‘Amdä Ṣǝyon I (1314–1344) and the Däbrä Libanos monastic congregation. The author argues that the second half of that verse was deliberately changed in order to make the royal marriage of ‘Amdä Ṣǝyon I to a wife/concubine of his late father to be seen as the mother – son incest. The conflict took place in the 27th year of the reign of ‘Amdä Ṣǝyon I. The new interpretation of the Lev. 18:8 as appears in the Kǝbrä nägäśt allows to attribute the treatise rather precisely: the terminus ante quem non can be set from the beginning of the 40s of the 14th century AD, i.e. somewhere in the 1340s.